2015
DOI: 10.1124/dmd.114.061127
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Pharmacokinetics of Primaquine in Healthy Human Volunteers

Abstract: Primaquine (PQ), a racemic drug, is the only treatment available for radical cure of relapsing Plasmodium vivax malaria and blocking transmission of P. falciparum malaria. Recent studies have shown differential pharmacologic and toxicologic profiles of individual PQ enantiomers in rodent, dog, and primate animal models. This study was conducted in six healthy adult human volunteers to determine the plasma pharmacokinetic profile of enantiomers of PQ and carboxyprimaquine (cPQ), the major plasma metabolite. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 43 publications
6
32
0
Order By: Relevance
“…Substrate concentrations, as initially titrated, showed optimal metabolism at 20 µM (Km = 37 µM). Although this is higher than expected peak plasma concentrations in humans as we earlier reported (<2 µM) [ 15 ], it approximates expected liver concentrations of PQ, which we observed to be—at therapeutic doses about 20 times higher than plasma in our studies in mice [ 22 ]. The viable cell counts in the drug-free incubation at the predetermined time-points were similar to those of the PQ-containing incubates, suggesting the absence of PQ-induced direct hepatocellular toxicity (Fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Substrate concentrations, as initially titrated, showed optimal metabolism at 20 µM (Km = 37 µM). Although this is higher than expected peak plasma concentrations in humans as we earlier reported (<2 µM) [ 15 ], it approximates expected liver concentrations of PQ, which we observed to be—at therapeutic doses about 20 times higher than plasma in our studies in mice [ 22 ]. The viable cell counts in the drug-free incubation at the predetermined time-points were similar to those of the PQ-containing incubates, suggesting the absence of PQ-induced direct hepatocellular toxicity (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Oxidation of PQ by MAO results in formation of an aldehyde metabolite, which is further oxidized or reduced to the stable metabolites namely, carboxyprimaqine (CPQ) and PQ-alcohol, respectively. CPQ had been identified as the major circulating human metabolite of racemic PQ [ 14 , 15 ]. Pharmacokinetic studies of racemic PQ in mice, monkeys and humans have shown that CPQ rapidly appeared in the plasma and was predominantly the (−)-form [ 9 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 a role in the metabolism that occurs both in vitro and in vivo (Fasinu, et al, 2014;Tekwani, et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent studies of PQ metabolism have revealed interesting new information about the metabolic pathways, suggesting that in humans the two enantiomers of PQ (which is used as a racemic mixture) are differentially metabolized to CPQ [ 20 ]. While the R (–) form of PQ is readily converted to CPQ, the S (+) form is much less so, and in fact >95 % of the CPQ circulating is attributable to R (–) PQ.…”
Section: Introductionmentioning
confidence: 99%